(untitled) (Journal of Engineering, 2005)
Corrosion of carbon steel pipe in aerated 0.1N NaCI solution nder isothermal turbulent flow conditions (Reynolds number 15000-113000 and temperature of 30-60°C) is investigated by weight loss method. The effect of Reynolds number and temperature on corrosion rates is experimentally studied and discussed. Corrosion mechanism is analyzed as a mass transfer operation and the corrosion rate is expressed in terms of mass transfer dimensionless groups (Sh and St) and in terms of usual corrosion units. The results of corrosion rates are compared with many proposed models particularly those based on the concept of analogy among mass, heat, and momentum transport by determining experimental friction factor. The capability of these models to express corrosion rates over the investigated range of Re and temperature is examined and discussed. Many of these correlations are adopted to estimate corrosion rates for the considered system. It is found that Reynolds number increases the corrosion rate depending on temperature. Temperature increases the corrosion rate for high and moderate values of Reynolds number. At low Reynolds number the effect of temperature depends on oxygen solubility, oxygen molecular diffusivity, and Reynclds number (or eddy diffusion). Generally, Von Karman and Prandtl-Taylor analogies (based on the experimental friction factor) show good agreement with experimental mass transfer results while Chilton-Colburn analogy exhibits reasonable agreement at low Reynolds number and some overestimation at high Reynolds number